2015
DOI: 10.3390/ma8105341
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Field Enhancement in Plasmonic Waveguides for Subwavelength Light-Guiding, Polarization Handling, Heating, and Optical Sensing

Abstract: Plasmonic nanostructures have attracted intensive attention for many applications in recent years because of the field enhancement at the metal/dielectric interface. First, this strong field enhancement makes it possible to break the diffraction limit and enable subwavelength optical waveguiding, which is desired for nanophotonic integrated circuits with ultra-high integration density. Second, the field enhancement in plasmonic nanostructures occurs only for the polarization mode whose electric field is perpen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 113 publications
(199 reference statements)
0
16
0
Order By: Relevance
“…Besides, these attractive nanoplasmonic modal natures with different light guiding conditions gives intuitive ideas in design and fabrication of complex plasmonic devices, such as logic gates, switch, BUS router, modulator and nanowire laser. An appropriate selection of background dielectric materials and metal nanowire design parameters could lead to control the long-range subwavelength confined plasmonic modes and their incorporation in compact integrated plasmonic and hybrid plasmonic active and passive nanophotonic circuits [21], [22], polarization controlling devices [7], [22], nonlinear [23] and sensing [8], [9], [22], [24] applications. From 1976 to 1979, he was a Lecturer in the Department of Electrical Engineering, BUET.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, these attractive nanoplasmonic modal natures with different light guiding conditions gives intuitive ideas in design and fabrication of complex plasmonic devices, such as logic gates, switch, BUS router, modulator and nanowire laser. An appropriate selection of background dielectric materials and metal nanowire design parameters could lead to control the long-range subwavelength confined plasmonic modes and their incorporation in compact integrated plasmonic and hybrid plasmonic active and passive nanophotonic circuits [21], [22], polarization controlling devices [7], [22], nonlinear [23] and sensing [8], [9], [22], [24] applications. From 1976 to 1979, he was a Lecturer in the Department of Electrical Engineering, BUET.…”
Section: Discussionmentioning
confidence: 99%
“…This approach ensures minimal energy loss in the metal and maximum propagation length. Notably, in contrast to hybrid dielectric-loaded plasmonic waveguides [35,36], which are created to achieve the best trade-off between the mode confinement and propagation loss, our multilayer system is designed to achieve minimal propagation loss (even at the cost of the mode confinement). More information on designing LRSP-supporting structures with two metal layers can be found elsewhere [24].…”
Section: Field Profilesmentioning
confidence: 99%
“…However, the TM-pass polarizer offers insertion losses of 1 dB, extinction ratio of 20 dB with compact device length of 2.84 µm. Dai et al [13] have also reported the recent progresses of the plasmonic nanostructures usage for different applications such as waveguiding, polarization handling, heating, and optical sensing. Additionally, different numbers of polarization beam splitters and rotators have been demonstrated by many researchers [14][15][16].…”
Section: Introductionmentioning
confidence: 97%